The Use of the Natuna Game About the Natural Wealth of the Natuna Marine on National Awareness of the Post-Millennial Generation - Ibrahim, Intan Maharani; Suryadi, Karim; Darmawan, Cecep; Nurbayani, Siti (ASEAN Journal of Science and Engineering, 2024)
This research aims to explain the influence of using Natuna games in understanding natural wealth on the national consciousness of the post-millennial generation (Gen-Z). The method used is Design-based Research, through the stages of analysis, design, development, and evaluation. The results of the research are in the form of Game Natuna. Several validation tests were carried out on the product, namely in terms of material, media, and readability for representatives of the Gen-Z with a validation percentage in terms of material, media, and readability respectively of 95.22, 90.25, and 92.60%. Apart from that, a media implementation was also carried out on 80 Gen-Z people, where the results showed there was a significant difference in national awareness of Gen-Z who used Natuna games compared to Gen-Z who did not use Natuna games. Where students who use the Natuna game have an average national awareness score of 84.10, while those who don't use the Natuna game have an average score of 81.60. It can be concluded that the game Natuna Media developed is very suitable for use and is expected to increase awareness across generations in maintaining national resilience. It is recommended for further research to develop the Natuna game more widely and increase the sense of national awareness.